Chemistry Teachers’ Perspectives to Enchancing Representational Competence in Learning Thermochemistry - Rosyida, Ima; Widarti, Hayuni Retno; Yahmin, Yahmin (FKIP Universitas Lampung, 2024)
Representational competence is very essential for students because it is associated with the students' ability to use, interpret, translate and integrate chemical representations to understand chemical concepts properly. In this case, implementation of the various representations utilization is required in learning Thermochemistry to improve students' representational competence to fully understand Thermochemistry. Therefore, this study aims to analyze teachers' perceptions towards the understanding and implementation of chemical representations in chemistry learning to improve students' representational competence in thermochemistry. This research is a descriptive quantitative research conducted using survey method that involved 30 chemistry teachers. The sample in this study was taken by purposive random sampling at public and private high schools in East Java. The data were collected through a questionnaire using google form application. According to the results of the study 63.3% of teachers still have difficulty in teaching students the concept of thermochemistry using submicroscopic representations. The majority of teachers only use symbolic representations, even though the other two representations are very important. Although 77% of teachers have understood chemical representations, in teaching and measuring concept understanding, teachers have not integrated chemical representations. This is due to their lack of self-awareness about the importance of using various representations in improving students’ representational competence. Thus, training on representations is necessary in improving teachers’ understanding on chemical representations. The findings of the study stated that teachers’ understanding of representation and teachers’ experience in participating in the trainings contributed to the effectiveness of the implementation of various chemical representations utilization to improve students’ representational competence on the concept of thermochemistry. Keywords: representational competence, chemical representation, and thermochemistry.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1559-1576